Frequency of ABO Blood groups in patients with Diabetes (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background and Objectives: The objective of this study was to evaluate the frequency of the ABO blood groups in sample of patients diagnosed  with Diabetes Mellitus in Gujarat population. Methods: Case - control study. The study has been carried out in Patients reporting to Medicine department and donor of  blood bank of Dhiraj General Hospital, SVU, Pipariya, Vadodara, Gujarat. The study included total 400 patients  above 18 years of age were selected, out of which 200 were normal healthy controls (nondiabetic) and 200 patients  with diabetes. Blood samples were collected from the Patients after consent had been obtained, thus giving the  response rate of 82.4 %. The ABO blood groups of all subjects were determined and recorded by Slide  Agglutination method at Haematology laboratory and Blood bank. Results: Data were analysed by “one sample chi square test”. The x² test results showed that there was association between  the frequency of ABO blood group and Diabetes Mellitus. The data revealed that the blood group B was  significantly more common in diabetic patients as compared with Non-diabetic healthy population (25.5% vs.  23.5%; P < 0.001). Blood group O was significantly less common in diabetic patients compared with non-diabetics  (38.5% vs. 44.5%; P < 0.001). Among diabetic men, the frequency of only blood group B was significantly higher,  while on the contrary among diabetic women the frequency of both A and B (29.8% vs. 25%; P = 0.033 and  25.7% vs. 19.7%; P < 0.0087, respectively) were significantly higher as compared with nondiabetic healthy  population. Conclusion: Our study confirms that the frequency and association exist between the blood group and type of Diabetes Mellitus  in this Gujarat population. The findings in this study suggest that ABO antigens are associated with DM. DM is  more common in individuals with blood group B. Therefore, a larger extensive study is needed to establish the  correlation.
Keywords: ABO Blood groups; Diabetes Mellitus; Gender; Case-control